AB0386 Infection as a Comorbidity in a Cohort of Rheumatoid Arthritis Patients from Clinical Immunology Unit – Centro Hospitalar do Porto. (9th June 2015) - Alves, R.F.; Lima, S.; Faria, R.; Machado, A.; Lopes, J.; Costa, R.; Brandão, M.; Vasconcelos, C.
Abstract : Background: Rheumatoid Arthritis (RA) is known to be associated with an increased risk of serious infection. The elevated susceptibility of patients with RA can be explained by the pathobiology of the disease itself, the impact of chronic comorbid conditions, as well as side effects of immunosuppressive treatment 1 . Objectives: The aim of this study was to understand the impact of RA and its therapies in the risk of development of serious infection in a cohort of our outpatient clinic. Methods: Out of the almost 450 RA patients of our cohort, a retrospective analysis of prospectively collected data from clinical charts of RA patients observed in the outpatient clinic between January-June 2013 was performed. Three hundred and nineteen patients' charts with definite 2010 ACR RA classification criteria were reviewed for duration of disease, immunosuppressive agents currently or formerly used and occurrence of severe infection (defined as opportunistic and/or those with admission criteria). Statistics analysis was performed using SPSS™ v21.0. Results: Of the 319 RA patients reviewed, 253 (79, 3%) were women with a mean age of 48, 6 years, a mean follow-up time of 6, 2 years (min 0, 03yr, max 32, 67yr) and a mean age at diagnosis of 48, 8 years. 2 (6, 6%) patients had at least one other autoimmune disease, most frequently Sjögren syndrome (10, 47, 6%) and Systemic Lupus Erythematosus (6, 28, 6%). Main immunomodulators currently or formerly used: methotrexate in 271 (86%); steroids in 277 (82, 2%); hydroxychloroquine in 170 (54, 8%), salazopyrine in 95 (30, 4%). There were 28 infections in 21 (6, 6%) patients, 2 of which opportunistic, and all of them required hospital admission. Mean age at first infection was 57, 6 years, with a mean follow-up time of 7, 78 years. Non-opportunistic severe infections: 14 (50%) were respiratory, 8 (29%) genitourinary tract and 3 (11%) skin infections. The etiologic agent was identified in 18 (64%) cases, most frequently bacteria (89%). Of the two opportunistic infections, one was a Mycobacterium avium respiratory infection and the other one was a bacterial disseminated infection. The risk of infection correlated positively with the use of rituximab [HR 3, 85, (95CI 1, 02; 14, 58)], leflunamide [HR 4, 68, [95CI 1, 54;14, 10)] and adalimumab [HR 4, 23, [95CI 1, 49;11, 98)] and negatively with the use of hydroxychloroquine [HR 0, 31, (95CI 0, 10;0, 94)]. There was no correlation between the use of other immunomodulators and infection. Conclusions: Infection remains an important comorbidity in RA patients as severe infection occurred in 6, 6% of our RA patients. The types of infections in RA patients are similar to the general population and include the same pathogens. There was increased risk of infection with the use of rituximab, adalimumab and leflunamide, and a protective effect of hydroxychloroquine. This prevalence of infection is underestimated since only alive patients that come to the outpatients clinic were assessed. References: Listing J, Gerhold K, Zink A. The risk of infections associated with rheumatoid arthritis, with its comorbidity and treatment. Rheumatology (Oxford). 2013 Jan;52(1):53-61. doi: 10.1093/rheumatology/kes305. Epub 2012 Nov 28. Disclosure of Interest: None declared